Hukum Sholat Sunnah di Iqamah - Amanda Amanda; Layli Sartika; Merli Anggelia; Naila Hafizah; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
Adhan is a call for Muslims to perform fardhu prayers. Iqamah is a notification call to the congregation to be ready to stand up for prayer, with the pronunciation determined by the syara'. Adhan and iqamah are very important for every Muslim. Apart from that, the call to prayer is said as a sign that the prayer time has arrived and the iqamah as a sign that the prayer will begin soon. The call to prayer and iqamah should not be done haphazardly, unlike other religious prayers. The call to prayer and iqamah are said at certain times. The lessons learned from the implementation of the call to prayer and iqamah include: As a tool and medium for notification of the approaching prayer time, inviting Muslims to perform prayers in congregation. Adhan and iqamah cannot be separated from the life of Muslims and Muslim women. Its use is not limited to obligatory prayers and certain times when they are said. If the iqamah has been said before he starts the sunnah nafilah prayer then his sunnah prayer is invalid. It is permissible to decide to pray the sunnah nafilah prayer because the obligatory prayer is not comparable in value to the nafilah prayer.